From Cartel to Courtroom: Integrating Competition Leniency into the Justice Collaborator Framework for Effective Bid Rigging Prosecution - Jaden Asher Marpaung; Yuni Priskila Ginting (CV. AFDIFAL MAJU BERKAH, 2026)
Bid rigging causes massive losses to Indonesia's State Budget accounting for 70 percent of procurement corruption cases. However, proving these cases remains extremely difficult because they rely on rare internal corporate testimony. This normative juridical study proposes adapting competition law's leniency program into anti-corruption frameworks following Government Regulation No 24 of 2025 on special handling and rewards for witnesses and perpetrators. Through statute conceptual comparative and case approaches findings reveal bid rigging's secretive nature exemplified by pier tender collusion cases necessitates corporate immunity incentives currently absent under corruption law Article 20 and corporate law Article 97 paragraph 3. The leniency mechanism supports follow the money and follow the suspect approaches essential for state budget recovery. Digital era adaptations become crucial as modern bid rigging uses Zoom WhatsApp coordination and PDNS tender manipulations demanding KPPU-KPK digital integration through KPPU Mendengar platform AI evidence analytics and blockchain procurement audit trails. Keywords: bid rigging, tender collusion, leniency program, corruption